Assessment of economic loss due to fish diseases in Assam, India and implications of farming practices - Debnath, Dipesh; Manna, S K; Devnath, D J; Payeng, L K; Das, Nilemesh; Bandyopadhyay, C; Yengkokpam, Sona; Das, B K; Bhattacharya, B K; Patil, P K (Journal of the Inland Fisheries Society of India, 2021)
Extensive surveys were conducted in 60 fish farms in Cachar and Nagaon districts of Assam, India to assess economic loss due to aquatic animal diseases and the contribution of fish farming practices therein. Epizootic Ulcerative Syndrome (EUS), also known as mycotic granulomatosis or red spot disease, was the most common disease that affected most fish species during winter months. Other disease conditions reported were dropsy, fin/tail rot and Argulus infestation. Overall disease prevalence was less in Cachar district compared to that in Nagaon district. Estimated loss of fish production (as percentage of total production) and total economic loss (in INR) were estimated to be 10.8% & 67,500.0 per farm (30,770.0 per ha) in Cachar and 5% & 55,300.0 per farm (14,900.0 per ha) in Nagaon district.The average farm area, water area and the number of ponds (per farmer) were less in Cachar compared to that in Nagaon district. Average fish production was also lower (1870 kg ha-1) in Cachar compared to Nagaon (2470 kg ha-1). The majority of fish farms in Cachar (60%) operated as a nursery (N) and grow-out (G) systems whereas those in Nagaon operated as nurseryfingerling-growout (N-F-G) system (63.33%). An overwhelming majority of farmers (93.33%) in Cachar practiced polyculture, but 30% of farmers practiced integrated farming in Nagaon district. N-F-G farming system and integrated culture practice adopted by the majority of Nagaon farmers led to higher fish productivity and lesser economic loss. Poor pre-stocking management of fish ponds was found to be the main contributory factor for higher disease prevalence in Nagaon compared to that in Cachar district. However, the farmers in Nagaon district were more aware of disease control measures that resulted in moderate economic loss. Key words Aquaculture practices, Fish diseases, Economic loss, Assam